DEVELOPMENT OF NEW PRODUCT “COCOA SPIRULINA AS FUNCTIONAL FOOD” - Asmak Afriliana; Achmad Subagio; Aminah Abdullah (UNEJ e-Proceeding, 2016)
Cocoa spirulina is a beverage made by the blending of between cocoa, spirulina powder, and cream of coconut. The aim of the study was to determine the Cocoa Spirulina chemical characteristics, nutrient content (vitamin B complex), and functional properties (antioxidants and polyphenols) that can be used as a reference in its application to the food industry. Cocoa Spirulina formulation used is the ratio of spirulina and cocoa powder in a row; it is put 2: 10; 1.5: 10; and 2: 10. The Data of the water content are 5.8 - 6:07%. The Ash content are 4:18 to 4:51%. The Protein content of Cocoa Spirulina is smaller when compared to unfermented spirulina powder, 0.66-2.28%. The fat content are 8.94 - 11.66%. While the antioxidant power are 1:19 - 1,223 mmol / g, total phenolic content (TPC) are 12.81 - 13:32%. Phenolic and flavonoid compound are 8.47-28.47%, chlorogenic acid (11.86-18.53%), and syringic acid (5.45 to 6.49%) and epicatechin (1.67-2.98%). This product is presented using cold water and the best formulation is the second formulation. This is because the second formulation, nutritional and functional properties contained therein is completing (all detected), as well as in terms of taste is also still acceptable.